2008
DOI: 10.1002/jobm.200800197
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Penicillium chrysogenum antifungal protein (PAF) on barley powdery mildew and wheat leaf rust pathogens

Abstract: The small molecular mass antifungal protein of Penicillium chrysogenum (PAF) inhibited the growths of two obligate biotrophic fungal pathogens, Blumeria graminis f. sp. hordei and Puccinia recondita f.sp. tritici and, hence, mitigated the symptoms of barley powdery mildew and wheat leaf rust infections, respectively. PAF also affected adversely the germination of B. graminis conidia and P. recondita uredospores causing degenerative branching of germ tubes. Since powdery mildews and rusts cause serious economic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 20 publications
1
14
1
Order By: Relevance
“…The germ-tubes, if present, were truncated and many showed abnormal growth. The results support Barna et al (2008) who showed the antifungal peptide PAF from Penicillium chrysogenum had a strong inhibitory effect on wheat leaf rust spores, including truncated and abnormal germ tubs (when present).…”
Section: Discussionsupporting
confidence: 85%
“…The germ-tubes, if present, were truncated and many showed abnormal growth. The results support Barna et al (2008) who showed the antifungal peptide PAF from Penicillium chrysogenum had a strong inhibitory effect on wheat leaf rust spores, including truncated and abnormal germ tubs (when present).…”
Section: Discussionsupporting
confidence: 85%
“…PAF represents a promising bio-molecule for novel antifungal drug development as it is stable against proteolytic degradation, thermo-resistant and active within a broad pH range 9 , and shows no cytotoxic effects in vitro 10 or in vivo 11 , 12 . Furthermore, PAF could serve as a potential bio-pesticide in agriculture to impede infection by plant-pathogenic fungi 13 .…”
Section: Introductionmentioning
confidence: 99%
“…tritici) and millet rust (P. substriata) was reduced significantly in transgenic wheat and millet plants that expressed afp (antifungal protein from Aspergillus giganteus) within the apoplast, relative to wild-type control plants (Girgi et al, 2006;Oldach et al, 2001). Other studies have reported that foliar applications of plant extracts derived from Tulbaghia violacea and Agapanthus africanus reduced the pustule number and density of leaf rust on barley leaves (Cawood et al, 2010;Barna et al, 2008). However, the active constituents responsible for control remain unknown.…”
Section: Introductionmentioning
confidence: 99%